Marine pollution and human health - Hester, R. E. (Ronald E.), editor; Harrison, R., editor (Cambridge : Royal Society of Chemistry)
Marine Environment and Human Health: an Overview / J. Icarus Allen -- Waterborne Pathogens / Jill R. Stewart [et. al.] -- Estuarine and Marine Pollutants / James W. Readman [et. al.] -- Harmful Algal Blooms / Keith Davidson, Paul Tett and Richgard Gowen -- Scientific Challenges and Policy Needs / Michael N. Moore, Richard Owen and Michael H. Depledge.